(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
This study aims to address the phenomenon of sisyphism in Marwan Al-Khater’s poetry, as an artistic phenomenon that has a clear impact on the poet’s works; because the Greek myth (the myth of Sisyphus) carried in the poet’s subconscious a semantic momentum and deep contents that provoked his depths and inspired him the ability to intensify his poetic vision in a symbolic way that accommodates the dimensions of his contemporary experience. This study is based on addressing this artistic phenomenon in Marwan Al-Khater’s poetry as an independent phenomenon that has not been analyzed and studied before, the researcher examines it with a descriptive analytical approach by revealing the various connotations of sisyphism and knowing the mechanism of its manifestation and how to employ it.